Human immunodeficiency virus 1 (HIV-1)-specific reverse transcriptase (RT) inhibitors may suppress the replication of specific drug-resistant (E138K)RT HIV-1 mutants or select for highly resistant (Y181C-->C181I)RT HIV-1 mutants. - Balzarini, J (1994)
Mutant HIV-1 that expresses a Glu138-->Lys substitution in its RT [(E138K)RT] is resistant to the HIV-1-specific RT inhibitor 2',5'-bis-O-(tert-butyldimethylsilyl)-3'-spiro-5"-(4"-amino-1",2"- oxathiole-2",2"-dioxide)pyrimidine (TSAO). However, cell cultures infected with this mutant were completely protected against virus-mediated destruction by micromolar concentrations of the HIV-1-specific RT inhibitors tetrahydroimidazo[4,5,1-jk][1,4]benzodiazepin-2(1H)-one and -thione (TIBO), nevirapine, and bis(heteroaryl)piperazine (BHAP). In contrast, cells infected with a virus mutant that expresses a Tyr181-->Cys substitution in its RT [(Y181C)RT] were not protected by nevirapine and TIBO and were only temporarily protected by BHAP. HIV-1 mutant that emerged under the latter conditions contained a Cys181-->Ile substitution in their RT [(LC181I)RT]. This mutant proved highly resistant to all HIV-1-specific RT inhibitors tested, except for several 1-(2-hydroxyethoxymethyl)-6-(phenylthio)thymine (HEPT) derivatives. When recombinant (C181I)RT was evaluated for susceptibility to the HIV-1-specific RT inhibitors, it was resistant to all inhibitors except the HEPT compounds. Since a (Y181F)RT HIV mutant strain was isolated from cells infected with (Y181C)RT HIV-1 and treated with BHAP, we postulate that the Ile codon was derived from a Cys-->Phe transversion mutation (TGT-->TTT), followed by a Phe-->Ile transversion mutation (TTT-->ATT).